2022
DOI: 10.1177/09612033221102073
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, safety, and antiphospholipid antibodies after SARS-CoV-2 vaccine in patients with primary antiphospholipid syndrome

Abstract: Objective Coronavirus disease 19 (COVID-19) has an increased risk of coagulopathy with high frequency of antiphospholipid antibodies (aPL). Recent reports of thrombosis associated with adenovirus-based vaccines raised concern that SARS-CoV-2 immunization in primary antiphospholipid syndrome (PAPS) patients may trigger clotting complications. Our objectives were to assess immunogenicity, safety, and aPL production in PAPS patients, after vaccinating with Sinovac-CoronaVac, an inactivated virus vaccine against C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…Two surveys in patients with aPL antibodies reported that COVID-19 vaccination did not result in severe adverse events [ 18 , 19 ]. A study reported that COVID-19 vaccine did not affect aCL and anti-β2GP1 IgG and IgM titres in primary APS patients [ 20 ]. A step further, our study is the first prospective study designed to evaluate the comprehensive autoimmune antibody profile (including anti-PF4-heparin antibodies) as well as clinical pictures in pre- and post-vaccinated primary APS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two surveys in patients with aPL antibodies reported that COVID-19 vaccination did not result in severe adverse events [ 18 , 19 ]. A study reported that COVID-19 vaccine did not affect aCL and anti-β2GP1 IgG and IgM titres in primary APS patients [ 20 ]. A step further, our study is the first prospective study designed to evaluate the comprehensive autoimmune antibody profile (including anti-PF4-heparin antibodies) as well as clinical pictures in pre- and post-vaccinated primary APS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The used assays were Sure-Vue rapid plasma reagin (RPR) test, (Thermo Fisher Scientific, Waltham, MA, USA) and Macro-Vue RPR test (Becton Dickinson) [118]. These data have been validated by other groups, including no modification in previous positive intensity before and after vaccination in patients suffering from APS [119,120]. Despite this, larger longitudinal studies are needed to determine the incidence and window of false reactivity.…”
Section: Antiphospholipid Syndrome and Covid-19 Vaccinesmentioning
confidence: 99%
“…Borghi et al have reported that vaccination may trigger low titre autoantibody production, including anti-phospholipid antibodies, in health care workers [44]. In contrast, a recent study looking into the dynamics of auto-antibodies after SARS-CoV-2 vaccination in patients with antiphospholipid syndrome, did not observe a statistically significant increase of beta-2 glycoprotein 1 [45]. Moreover, we found an increase in antibodies against nucleosome, which is the cardinal antigen implicated in the pathogenesis of systemic lupus erythematosus [46] and an increase in antibodies against SPLUNC2 which belongs to an extended group of proteins expressed in the upper airways, nose and mouth, for which little is known [47].…”
Section: Discussionmentioning
confidence: 96%